2020
DOI: 10.3390/ijerph17093180
|View full text |Cite
|
Sign up to set email alerts
|

Association between Living with Children and the Health and Health Behavior of Women and Men. Are There Differences by Age? Results of the “German Health Update” (GEDA) Study

Abstract: Does the health of women and men living with and without minor children differ, and are age differences evident in the association? For self-rated general health, depression, back pain, overweight, smoking and sporting inactivity, the GEDA data 2009–2012 (18–54 years, n = 39,096) were used to calculate prevalence for women and men stratified by parental status (living with children: yes/no) and age. Moreover, we calculated odds ratios and predictive margins, performing logistic regressions with interaction ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 106 publications
(168 reference statements)
2
10
2
Order By: Relevance
“…The results of this study indicate that fatherhood is associated with sport index and being active in sports in adults aged 45 and older. Higher levels of physical activity among elderly parents compared to non-parents were also reported by earlier studies [7,14], although this question has received scant attention in the previous literature. It is interesting to note that this result is contrary to research in younger parents, which has suggested decreased physical activity levels in parents when compared to their childless counterparts [8][9][10][11][12][13]15].…”
Section: Physical Activity In Sportsmentioning
confidence: 69%
See 3 more Smart Citations
“…The results of this study indicate that fatherhood is associated with sport index and being active in sports in adults aged 45 and older. Higher levels of physical activity among elderly parents compared to non-parents were also reported by earlier studies [7,14], although this question has received scant attention in the previous literature. It is interesting to note that this result is contrary to research in younger parents, which has suggested decreased physical activity levels in parents when compared to their childless counterparts [8][9][10][11][12][13]15].…”
Section: Physical Activity In Sportsmentioning
confidence: 69%
“…Previous research has focused often on health behaviour among parents of young children. When compared to their childless counterparts, parents spent less time in moderate to vigorous physical activity [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. In terms of nutrition, some studies reported a slightly higher intake of energy and fat among parents [ 16 , 17 ], whereas other studies found no difference in dietary pattern between parents and childless individuals [ 11 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parents of children in this age group may therefore be receptive to interventions that encourage bicycling. Children may facilitate leisure-time physical activity among mid-aged parents generally ( Rattay and von der Lippe, 2020 ); recreational bicycling may be well-suited for family-oriented leisure-time physical activity.…”
Section: Discussionmentioning
confidence: 99%